Problems and Alternative Solution in Translating Arabic Texts among Students at Secondary School - Adinda, Dea; S, Fahrurrozi. (Universitas Muhammadiyah Sumatera Barat, 2025)
This study aims to identify the problems faced by Grade IX-C students of SMP IT Al-Hijrah Medan in translating Arabic texts into Indonesian, as well as to formulate appropriate alternative solutions to address these issues and potentially improve the students’ translation skills. The research employs a descriptive qualitative approach with a case study method, using data collection techniques such as observation, interviews, and documentation of students’ translation test results. The findings indicate that the problems encountered by students fall into two categories: linguistic and non-linguistic problems. In terms of linguistic aspects, students struggle with limited understanding of Arabic grammar structures, unfamiliarity with reading Arabic texts, a lack of vocabulary mastery, and a tendency to translate texts literally. Meanwhile, the non-linguistic issues include low motivation and interest among students, lack of variety in teaching methods, insufficient practice time, limited learning media, and students’ educational backgrounds. Moreover, the alternative solutions proposed by the researcher as a contingency plan to address these issues include the development of contextual and interactive learning models, the enhancement of teacher competencies alongside the implementation of well-structured instructional strategies, and the gradual habituation of students to text reading and analysis.